Long-term outcomes of drusenoid retinal pigment epithelium detachment in eyes with age-related macular degeneration - Sinem Karabulut; Sema Tamer Kaderli; Aylin Karalezli (Indian Journal of Ophthalmology, 2025)
Purpose: We aim to evaluate the changes in the size of drusens and drusenoid pigment epithelial detachments (PED) in patients with age-related macular degeneration. Design: This study was designed as an observational retrospective cohort study. Methods: We evaluated eyes with drusenoid PED tracked using spectral-domain and enhanced depth imaging optical coherence tomography. The cases were classified according to the follow-up visits and divided into two groups as eyes with collapsed PED and persisting PED. The best-corrected visual acuity (BCVA), size of drusens and PED, central macular thickness (CMT), and subfoveal choroidal thickness (SCT) were recorded. Results: We included 11 patients’ 22 eyes with drusenoid PED. In the final comparison, the mean CMT, SCT, and BCVA were significantly lower in Group 1 compared to Group 2 (P = 0.05; P = 0.05; P = 0.002, respectively). The mean CMT, SCT, and BCVA were significantly decreased from baseline to the last visit in Group 1 (P = 0.013; P < 0.001; P = 0.001, respectively). No significant changes were observed regarding the mean CMT, SCT, and BCVA in Group 2 during the follow-up visits. (P = 0.317, P = 0.682, P = 0.056). Conclusion: Spontaneous collapse of drusenoid PED is associated with poor visual outcome.